(untitled) (American Journal of Medical Science and Innovation, 2025)
The presence of unilateral optic disc swelling (ODS) is linked to several illnesses, such as hypertension and diabetes mellitus. While the incidence of diabetes is increasing in Bangladesh, not much is known about its systemic links in the local population. This study aims to evaluate the relationships between systemic factors and unilateral optic disc swelling among people in Bangladesh. A cross-sectional observational study was done at the Neuro-Ophthalmology Department in Dhaka from March 2019 to July 2020, covering 105 patients with unilateral ODS. Eye health was evaluated clinically, visual functioning was measured, and brain scans were performed for diagnosis. Basic demographics, historical details, and results from blood tests (CBC, RBS, HbA1c, lipid profile, CRP) were all collected with the use of structured forms. The statistical analysis was done using SPSS version 26.0, and the level of significance was p<0.05. NAION was the leading cause (40.95%), with optic neuritis (25.71%) coming next, and Pseudo Foster Kennedy syndrome (12.38%). About half of the patients (52.38%) had hypertension, and about three-quarters of all patients (42.86%) had diabetes, with around one-quarter (26.67%) having both conditions. The laboratory results showed that 46 patients (43.81%) had high blood pressure and 45 (42.86%) had elevated random blood sugar, matching what was found in their clinical records. Twenty-seven-point six percent of the population experienced abnormal lipid results, and 20.95% had raised HbA1c. Nearly half of the patients (45.72%) were seen for serious blindness (approximately 2 ft of vision). A visual field problem called an inferior altitudinal scotoma was prevalent among people with NAION. Almost half of the patients (49.52%) were not receiving treatment for their long-term medical issues. In neuro imaging findings, optic nerve enhancement & thickening was found in 26 patients (24.76%). There is a strong connection between hypertension and diabetes on one hand and unilateral optic disc swelling on the other. Early identification of systemic diseases and treating them promptly might prevent patients from losing sight.